Pre-hospital delay among patients with acute myocardial infarction in Saudi Arabia: A cross-sectional study - ALAhmadi, Ahmed F.; ALSaedi, Mohammed F.; Alahmadi, Abdullah E.; Alharbi, Mohammad G.; Alharbi, Ibraheem H.; Radman Al-Dubai, Sami A. (Saudi medical journal, 2020)
To estimate the pre-hospital delay time among patients diagnosed with acute myocardial infarction and to determine factors associated with pre-hospital delay. A cross-sectional study was conducted among 200 patients with myocardial infarction at Madinah Cardiac Center, Al Madinah Al Munawarah, Saudi Arabia between November 2019 and March 2020. Data were collected by direct physician-subject interviews. We used the validated version of the modified response to symptoms questionnaire. Chi-square test, t test, and multivariate analysis were used to examine factors associated with pre-hospital delay. The median pre-hospital delay time was 3.7 hours. Among all the patients, 126 patients (63%) arrived at the hospital later than 2 hours from the onset of symptoms. Factors that were significantly associated with pre-hospital delay included a previous information on acute coronary syndrome (adjusted odds ratio [adj OR]=0.35, 95% confidence interval [CI] 0.1-0.6), history of hypercholesteremia (adj OR=2.3, 95% CI 1.1-4.7), arrived by ambulance (adj OR=0.3, 95% CI 0.1-0.8), and increased pain intensity (adj OR=0.7, 95% CI 0.6-0.9). Approximately two-thirds of the patients arrived later than 2 hours from the onset of symptoms. A previous information about acute coronary syndrome, history of hypercholesteremia, arrived by ambulance, and increased pain intensity were associated with pre-hospital delay. The study recognizes the need for educational programs about acute myocardial infarction symptoms and the bene ts of availing an ambulance service.